Pelatihan Analisis Subyek dan Penentuan Notasi Bahan Pustaka Menggunakan DDC bagi Pengelola Perpustakaan STIT Darul Ulum Kubu Raya - Sahidi, Sahidi; Madete, Sisilya Saman; Hanum, Atiqa Nur Latifa; Amir, Amriani; Rahman, Miftah (Universitas Nusantara PGRI Kediri, 2024)
Library materials as information resources are the main issue of the existence of university libraries in providing services to users. The existence of library materials as information resources has a variety of formats that can provide knowledge for its users. However, the existence of library materials will certainly not provide maximum benefit to its users if the library materials are not well organized, because standard information organization will create a good information retrieval process or library materials. This community service activity aims to provide knowledge and skills in analyzing subjects and determining notation of library materials using DDC for library managers of STIT Darul Ulum Kubu Raya. This training uses the lecture method in the form of socialization and practice. The results of this activity showed that the participants were very enthusiastic about participating in the training, the participants were able to analyze subjects and determine the correct notation independently or in groups and they were interested in processing library materials independently using DDC. The participants who were library managers at STIT Darul Ulum Kubu Raya gained knowledge about techniques for analyzing subjects and determining notation of library materials using DDC. The participants also hoped that from this activity there would be further activities in the form of training in library material cataloging techniques.